An Overview on High-Performance Thin-Layer Chromatography (HPTLC) - Dharmamoorthy, Dr. G. (Asian Journal of Pharmaceutics (AJP), 2023)
High-performance thin-layer chromatography is one of the sophisticated instrumental techniques based on the full capabilities of thin-layer chromatography. The advantages of HPTLC are automation, scanning, optimization & computerization, selective detection, and minimum sample preparation. High-performance thin-layer chromatography (HPTLC) is useful in detecting chemicals of forensic concern. Various advance techniques in reference to HPTLC like hyphenations in HPTLC-MS, HPTLC-FTIR, and HPTLC-Scanning Diode Laser have made HPTLC a power analytical tool in the field of analysis. Applications of HPTLC include phytochemical and biomedical analysis, herbal drug quantification, active ingredient quantification, fingerprinting of formulations, and check for adulterants in the formulations. HPTLC is useful in detecting chemicals of forensic concern.